Mediasi Komitmen dalam Leadership dan Digital Entrepreneurial Intention yang Berpengaruh Terhadap Keberlanjutan Bisnis dan Keunggulan Kompetitif UMKM - Ristiaji Ari Wibowo; Dewie Tri Wijayati Wardoyo; Lilis Puspitawati (JEMBA, 2025)
This study aims to analyze the influence of Entrepreneurial Leadership and Digital Entrepreneurial Intention on business sustainability in Small Medium Enterprises, and to evaluate their impact on competitive advantage with organizational commitment as a mediating variable. This conceptual approach is based on a literature review of various relevant empirical and theoretical studies. The results of the study indicate that entrepreneurial leadership and digital entrepreneurial intention contribute significantly to business sustainability through increased innovation, adaptability, and long-term orientation. In addition, organizational commitment is proven to strengthen the relationship between independent variables and business sustainability. Effective business sustainability then has a positive effect on achieving a company's competitive advantage. These findings emphasize the importance of synergy between leadership, digital innovation, and internal commitment as a strategic foundation in building a resilient and highly competitive service business in the digital era